Chapter Il museo racconta la scuola tra passato e presente - BORRUSO, Francesca (Public History of Education. Teorie, esperienze, strumenti, 2022)
The Museums of educational heritage - especially those established in University Departments - represent an extraordinary resource for scientific research, education, and the Third Mission, which is aimed at promoting collaboration, dialogue and exchange between the University and its territory to generate knowledge and benefit of social, cultural, and economic nature as well. Within the Third Mission precisely lies Public History defined as "the communication of history outside academic environments" (AIPH 2018). In this framework the paper presents some examples of educational projects and activities carried out with local schools and communities by the "Mauro Laeng" Museum of school and education at the University of Roma Tre, and by the "Paolo & Ornella Ricca" Museum of school history at the University of Macerata. The final aim is to provide a methodological approach, project ideas, and operational tools for inspiring schoolteachers and professors, university researchers and museum educators.